Five cases of fatwa’s change in Majlis Tarjih Muhammadiyah - Azzam, Musoffa; Ghalia, Bouhedda; Artalim Zaim, Muntaha (Institut Agama Islam Negeri Palangka Raya, Indonesia, 2023)
Abstract: The purpose of this study is to understand the change of fatwa produced by Majlis Tarjih of Muhammadiyah Association from between their first establishment in 1927 until 2019. The study about the change of fatwa produced by them considered as important study for it may affect the life of not less than 10 million members of Muhammadiyah directly or indirectly. The board has announced 16 methods used in weighting issues including their confirmation of the probability of fatwa to be changed, it made the researcher curious for whether they can keep their own methods or not in case the fatwa has been changed. The researcher has used two methods in answering the problem; the first is analysis method, and it is used to analyze the collected fatwa from books and magazines produced by Majlis Tarjih. After analyzing the change of fatwa, the researcher tried to approach the change of fatwa from the view of Islamic jurisprudential maxims and Islamic control fundamentalist to know whether the cause of change is suitable to Islamic principle or not. The researcher has collected five changes of fatwa produced by them, and they are; 1) Considering matlak to determine the beginning of Arafah fasting, 2) bank’s interest, 3) Hanging the picture, 4) Smoking, 5) and using sitr (cover). The researcher has obtained number of findings; the most important of them is the fact that the change of fatwa in the cases mentioned were following their own methods and were suitable to Islamic principle.